Pulsatilla chinensis Saponins Ameliorate Inflammation and DSS-Induced Ulcerative Colitis in Rats by Regulating the Composition and Diversity of Intestinal Flora - Yali Liu (Frontiers Media S.A., 2021)
Pulsatilla chinensis (Bunge) Regel is a commonly used Chinese medicine for clearing away heat and detoxification, cooling blood, stopping dysentery, and anti-inflammatory effects. Pulsatilla chinensis saponins (PRS) have been identified to be responsible for producing these pharmacological activities. Studies have shown that Pulsatilla decoction has a good therapeutic effect on ulcerative colitis (UC), however, the therapeutic effect of PRS on UC has not been reported. Therefore, the purpose of this study was to investigate the possible anti-UC activity of PRS using a dextran sulfate sodium (DSS)-induced rat model, and further study the mechanism of PRS in the treatment of UC. The fecal and colon samples were collected from rats to monitor the changes in the composition and diversity of the intestinal flora, and pathological colon sections were also made to examine the mesenteric hemorheological characteristics. The results showed that PRS significantly reduced the mesenteric blood flow in UC rats and significantly alleviated the inflammatory response, which indicates that saponins are involved in the anti-UC effects of PRS. At the same time, it is also suggested that the regulation of intestinal flora by Pulsatilla chinensis saponins is an important pathway for its anti-UC activity, which may be ascribed to the increase in beneficial bacteria like norank_F_Muribaculaceae and norank_F_norank_O_Clostridia_UCG-014, and decrease in the harmful Bacteroides.